2022
DOI: 10.1016/j.tourman.2021.104399
|View full text |Cite
|
Sign up to set email alerts
|

Family support and posttraumatic growth among tourism workers during the COVID-19 shutdown: The role of positive stress mindset

Tuan Trong Luu

Abstract: The COVID-19 pandemic has taken a severe hit on the health of workers in the tourism industry. It is crucial to understand how to help the workforce in this service industry become resilient and adaptive through this crisis. The primary objective of this research is to examine how family support nurtures tourism workers' posttraumatic growth (PTG), an adaptation form in the resilience process. The valid data were collected from 384 tourism workers who were on unpaid leave or layoff during the COVID-19 crisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 103 publications
2
20
0
3
Order By: Relevance
“…It can serve as a buffer to the severity of the traumatic events and foster people's recovery from the difficulties (27). As a coping resource, empirical studies indicated that a higher level of support from family, friends, and significant others would predict a higher level of post-traumatic growth under the context of the COVID-19 pandemic (28)(29)(30). Meanwhile, perceived social support works as a protective factor in reducing depression and anxiety during the COVID-19 pandemic (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…It can serve as a buffer to the severity of the traumatic events and foster people's recovery from the difficulties (27). As a coping resource, empirical studies indicated that a higher level of support from family, friends, and significant others would predict a higher level of post-traumatic growth under the context of the COVID-19 pandemic (28)(29)(30). Meanwhile, perceived social support works as a protective factor in reducing depression and anxiety during the COVID-19 pandemic (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…People across generation, X, Y, Z have high intensity with smartphone even for increasing productivity (remote work) or personal matter such as entertainment particularly during this outbreak to keep themselves busy and distract their tense about COVID-19 threats. The previous studies found that people tend to distress during the outbreak with negative emotion such as feeling angry, easily get bored, laziness etc (Kimhi et al, 2020;Luu, 2022). However, there is a question whether they can cope the emotional damage with technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourism workers are the most directly affected because of the closure of tourism. They are faced with unpaid leave or dismissal during the crisis period [ 3 ]. Being frontline employees and always playing multiple roles during the journey, tour guides are an important part of the tourism industry in China, where organized tours still enjoy great popularity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature about the effects of COVID-19 on psychological behavior and employee performance in the hospitality industry remains scant [ 11 ]. It is unclear what kinds of impacts have been composed on tour guides’ physical and mental well-being, as well as their sustainable performance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation